Race : a history beyond black and white - Aronson, Marc. (New York : Ginee seo Books/Atheneum Books for Young Readers, 2007)
Race. You know it at a glance: he's black; she's white. They're Asian; we're Latino. Racism. I'm better; she's worse. Those people do those kinds of things. We all know it's wrong to make these judgments, but they come faster than thought. Why? Where did those feelings come from? Why are they so powerful?
Includes bibliographical references (p. 303-312) and index.
Ages 12 and up.
A Junior Library Guild selection
Keywords: Race -- History -- Juvenile literature; Racism -- History -- Juvenile literature; Race -- History; Racism -- History